Prevalence of metabolic syndrome in a Chilean pediatric population with overweight and obesity - Cesar Osorio-Fuentealba; Eduardo Cifuentes-Silva; Stefanie Arce-Pardo; Nicolas Acuña-Ordenes; Paulette Benavides-Ulloa; Camila Neira-Saldivia; Mauricio Inostroza-Mondaca (Boletín Médico del Hospital Infantil de México)
Background: Childhood obesity (OB) is a growing global concern, reflected in its increasing prevalence, and is one of the main causes of metabolic syndrome (MS) development. Due to the epidemiological relevance and associated complications of MS, it is necessary to conduct studies that provide local prevalence data. Our objective was to determine the prevalence of MS and the association of its components in a pediatric population with overweight (OW), obesity (OB), and severe OB (SOB). Method: This was a retrospective study. Data were collected from 122 participants, who were divided into three groups: OW, OB, and SOB. Anthropometry, lipid profile, glycemic control, and blood pressure (BP) were analyzed to assess intergroup differences and odds ratios (OR), along with a bivariate analysis. Results: The prevalence of MS was 40.1%. Triglycerides, high-density lipoprotein (HDL) cholesterol and BP showed differences between the OW and SOB groups. Fasting insulin, homeostatic model assessment (HOMA) index, systolic BP, and diastolic BP showed differences between the OW versus OB and OW versus SOB groups. Differences in ORs for MS occurrence were observed between OW versus OB (4.3), OW versus SOB (25.71), and OB versus SOB (5.7). There was an association between waist circumference, waist-to-height ratio, triglycerides, HDL cholesterol, systolic BP, fasting insulin, and HOMA index with the development of MS. Conclusion: The results of this study reveal that, locally, MS is characterized by significant differences in metabolic and anthropometric variables depending on the degree of excess weight. In addition, relevant associations were identified between specific MS components and OB severity, reinforcing the need for early diagnostic and preventive strategies in this population.